The risk of malignancy index (RMI) in diagnosis of ovarian malignancy: A case report - Daniel Anugrahta Sembiring; Renardy Reza Razali (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Ovarian cancer is among the deadliest gynecological cancers, with nearly 70% of cases identified at an advanced stage. It is the fourth most common cause of cancer-related deaths in women. While early detection significantly improves ovarian cancer outcomes, the disease often presents no symptoms in its early stages, resulting in delayed diagnosis and worsened prognosis. Achieving an accurate initial diagnosis in women with ovarian cancer is essential for ensuring early, correct treatment and reducing the risk of overtreatment. Clinically, various methods are available to assess ovarian malignancy risk, including the Risk of Malignancy Index (RMI). Purpose: To demonstrate the use of the RMI score to differentiate between benign and malignant ovarian tumors. Method: The case of Mrs. LKS, a 34-year-old woman who had experienced abdominal distension and related symptoms for one year, was analyzed in detail. The patient underwent multiple diagnostic evaluations, including a physical exam, ultrasound, abdominal CT scan, and histopathological analysis. The RMI, a well-established malignancy risk assessment tool, was employed. The initial evaluation of ovarian malignancy risk primarily considered ultrasound results, menopausal status, and serum CA-125 levels, with an RMI score above 200 indicating a high risk of ovarian cancer. Surgical procedures performed included a total hysterectomy, omentectomy, appendectomy, and ascitic fluid drainage. Results: The patient’s main issue was a gradually worsening abdominal distension over the past year, accompanied by lower abdominal pain, nausea, and significant weight loss. Physical examination and imaging revealed a heterogeneous cystic mass in the abdomen, suggesting a malignant ovarian cyst, along with the presence of ascites. The RMI score exceeded 200, indicating a high risk of ovarian malignancy. The patient underwent a laparotomy, which included a total hysterectomy, omentectomy, and appendectomy, leading to a postoperative diagnosis of stage III B ovarian cancer. Despite the intervention, the prognosis remained poor (dubia ad malam) due to the advanced stage at diagnosis. Conclusion: The RMI calculation serves as a valuable and reliable method for guiding diagnostic, management, and treatment decisions for patients with benign and malignant ovarian masses.